Gender specific differences in levels of DNA methylation at selected loci from human total blood - El Maarri, Osman (2007)
Abnormal patterns of DNA methylation are observed in many diseases such as tumors and imprinting disorders. Little is known about inter-individual and gender specific variations. Here, we report on accurate and sensitive quantitative measurements of methylation in DNA from total blood in 96 healthy human males and 96 healthy human females. Global methylation was estimated by studying two repetitive DNA elements, namely Line-1 and Alu repeats, while single loci were investigated for three differentially methylated regions (DMRs) at PEG3, NESP55 and H19 imprinted genes and two additional loci at Xq28 (F8 gene) and at 19q13.4 (locus between PEG3 and ubiquitin specific protease 29). We observed inter-individual correlations in the degree of methylation between Alu and Line-1 repeats. Moreover, all studied CpGs showed slightly higher methylation in males (P < 0.0003–0.0381), with the exception of DMRs at imprinted genes (P = 0.0342–0.9616) which were almost equally methylated in both sexes with only a small tendency towards higher methylation in males. This observed difference could be due to the process of X chromosome inactivation or merely to the presence of an additional X chromosome in female cells or could be a result of downstream effects of sex determination.